Tornel and Santa Anna : the writer and the caudillo, Mexico, 1795-1853 - Fowler, Will, 1966- (Contributions in Latin American studies, 2000)
"Makes persuasive case that José María Tornel y Mendívil, spin-doctor for Antonio López de Santa Anna, was an important figure in his own right, both as a politician and a writer. Emphasizes the 'great man' school of history, but forces the reader to conclude that the first political generation of independent Mexico boasted a substantial crew of extraordinary personalities"--Handbook of Latin American Studies, v. 58.